The accuracy of body mass prediction for elderly specimens: Implications for paleoanthropology and legal medicine. (October 2016) - Chevalier, Tony; Lefèvre, Philippe; Clarys, Jan Pieter; Beauthier, Jean-Pol
Abstract: Different practices in paleoanthropology and legal medicine raise questions concerning the robustness of body mass (BM) prediction. Integrating personal identification from body mass estimation with skeleton is not a classic approach in legal medicine. The originality of our study is the use of an elderly sample in order to push prediction methods to their limits and to discuss about implications in paleoanthropology and legal medicine. The aim is to observe the accuracy of BM prediction in relation to the body mass index (BMI, index of classification) using five femoral head (FH) methods and one shaft (FSH) method. The sample is composed of 41 dry femurs obtained from dissection where age (c. 82 years) and gender are known, and weight (c. 59.5 kg) and height are measured upon admission to the body leg service. We show that the estimation of the mean BM of the elderly sample is not significantly different to the real mean BM when the appropriate formula is used for the femoral head diameter. In fact, the best prediction is obtained with the McHenry formula (1992), which was based on a sample with an equivalent average mass to that of our sample. In comparison, external shaft diameters, which are known to be more influenced by mechanical stimuli than femoral head diameters, yield less satisfactory results with the McHenry formula (1992) for shaft diameters. Based on all the methods used and the distinctive selected sample, overestimation (always observed with the different femoral head methods) can be restricted to 1.1%. The observed overestimation with the shaft method can be restricted to 7%. However, the estimation of individual BM is much less reliable. The BMI has a strong impact on the accuracy of individual BM prediction, and is unquestionably more reliable for individuals with normal BMI (9.6% vs 16.7% for the best prediction error). In this case, the FH method is also the better predictive method but not if we integrate the total sample (i.e., the FSH method is better with more varied BMI). Finally, the estimation of the mean BM of a sample can be used with more confidence compared to the estimation of individual BM. The former is very useful in an evolutionary perspective whereas the latter should be used in keeping with the information gathered on the studied specimen in order to reduce prediction errors. Finally, the BM estimation can be a parameter to consider for personal identification. Highlights: Dry femurs from humans with known body mass were used in this study. Elderly sample is very useful to push prediction methods to their limits. Prediction of mean body mass of a human sample can be used with confidence. BMI has a strong impact on the accuracy of individual body mass prediction. The body mass estimation can be a parameter to consider for personal identification.